Nonspecific Effects of Infant Vaccines Make Children More Resistant to SARS-CoV-2 Infection - Luis Fonte; María Ginori; Gissel García; Yisel Hernández; Yaxsier de Armas; Enrique J. Calderón (MDPI AG, 2022)
A myriad of reasons, or a combination of them, have been alluded to in order to explain the lower susceptibility of children to SARS-CoV-2 infection and the development of severe forms of COVID-19. This document explores an additional factor, still little addressed in the medical literature related to the matter: nonspecific resistance to SARS-CoV-2 that could be generated by vaccines administered during childhood. The analysis carried out allows one to conclude that a group of vaccines administered during childhood is associated with a lower incidence and severity of SARS-CoV-2 infection among pediatric ages. Looking from an epidemiological perspective, this conclusion must be taken into consideration in order to ensure greater rationality in the design and implementation of prevention and control actions, including the administration of the COVID-19 vaccine, for these ages.